Impact of Steerable Sheaths on Contact Forces and Reconnection Sites in Ablation for Persistent Atrial Fibrillation. (8th December 2014) - ULLAH, WAQAS; HUNTER, ROSS J.; MCLEAN, AILSA; DHINOJA, MEHUL; EARLEY, MARK J.; SPORTON, SIMON; SCHILLING, RICHARD J.
Steerable Sheaths and Contact Force in AF Ablation Background In preclinical studies, catheter contact force (CF) during radiofrequency ablation correlates with the subsequent lesion size. We investigated the impact of steerable sheaths on ablation CF, its consistency, and wide area circumferential ablation (WACA) line reconnection sites. Methods and Results Five thousand and sixty‐four ablations were analyzed across 60 patients undergoing first‐time ablation for persistent AF using a CF‐sensing catheter: 19 manual nonsteerable sheath (Manual‐NSS), 11 manual steerable sheath, and 30 robotic steerable sheath (Sensei, Hansen Medical Inc.) procedures were studied. Ablation CFs were higher in the steerable sheath groups for all left atrial ablations and also WACA ablations specifically (P < 0.006), but less consistent per WACA segment (P < 0.005). There were significant differences in the CFs around both WACAs by group: in the left WACA CFs were lower with Manual‐NSS, other than at the anterior–inferior and posterior–superior regions, and lower in the right WACA, other than the anterior–superior region. There was a difference in the proportion of segments chronically reconnecting across groups: Manual‐NSS 26.5%, manual steerable sheath 4.6%, robotic 12% (P < 0.0005). The left atrial appendage/PV ridge and right posterior wall were common sites of reconnection in all groups. Conclusions Steerable sheaths increased ablation CF; however, there were region‐specific heterogeneities in the extent of increment, with some segments where they failed to increase CF. Steerable sheath use was associated with reduced WACA‐segment reconnection. It may be that the benefits of steerable sheath use in terms of higher CFs could be translated to improved clinical outcomes if regional weaknesses of this technology are taken into account during ablation procedures.